IMPROVING SPEAKING ABILITY THROUGH COMMUNITY-BASED LEARNING - Ambar Pujiyatno; Fitri Rakhmawati (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2016)
Speaking ability is very important to have good communication, especially in international communication. The English learners should have this ability and they must focus the learning on speaking skill. The learners’ failures in learning speaking were caused by the inappropriateness of the strategy or method learning. It happened to them unconciously. It means they are not aware of making inappropriateness in the method. The appropriate method should be applied in learning so that the success can be achieved. To realise the success in improving speaking ability can be done by using community-based learning method. The learning communities should be made to conduct the community-based learning. In these learning communities, the process of learning speaking can be appliead like it is in real communities. Real-like communities makes the learning process run well, because the condition is like the reality. The good process in learning makes the learners feel in the real society and feel enjoyable and confortable. If the learners have good feeling, they will learn speaking eagerly and spiritfully, so they will be succesfull in learning, especially speaking. Key words: Speaking, community-based, and learning